'Metodologias no Sahara' (Comentários Críticos sobre Ewa Strzelecka e Enrique Bengochea Tirado) - Oneill, B. (CAPSAHARA Research Seminar - Research Notes from Nouakchott and Tindouf: Islam, Politics, and Gender in the Sahara (coord. Francisco Freire), FCSH; 11 de Maio, 2018)
Comment on the ongoing fieldwork by two researchers in the ethnography of the Western Sahara, including studies of refugee camps. The role of gender in the ethnographer's local activities. Methodologies of interviewing in unstable conditions.